Perivascular parenchymal extension of the ablation zone following liver microwave ablation. (31st March 2016) - Singh, Saurabh; Siriwardana, Pulathis Nilantha; Johnston, Edward William; Bandula, Steven; Davidson, Brian Ritchie; Illing, Rowland Oliver
Abstract : A 69-year-old man who presented with abdominal discomfort was, on examination, found to have a palpable abdominal mass. Contrast-enhanced CT showed a mass arising from the inferior vena cava, which biopsy confirmed to be a leiomyosarcoma. One month after chemoradiotherapy, CT demonstrated a new 15 mm solitary central right liver metastasis. Microwave ablation (MWA) of the metastasis was performed using an Acculis Sulis V system (Angiodynamics, USA) at a power of 140 Watts for 4 min, with no immediate complications. After 1 month, MRI with gadolinium was performed to assess the liver ablation zone. The MRI demonstrated thrombosis of a right inferior hepatic vein branch leading to the ablation zone and extension of the ablation zone 1 cm into the tissue around the thrombosed vessel.